Wheat IgE profiling and wheat IgE levels in bakers with allergic occupational phenotypes. Issue 9 (17th May 2013) - Olivieri, Mario; Biscardo, Carlo Alberto; Palazzo, Paola; Pahr, Sandra; Malerba, Giovanni; Ferrara, Rosetta; Zennaro, Danila; Zanoni, Giovanna; Xumerle, Luciano; Valenta, Rudolf; Mari, Adriano
Abstract : Objectives: To characterise occupational wheat allergic phenotypes (rhino-conjunctivitis, asthma and dermatitis) and immunoglobulin (IgE) sensitisation to particular wheat allergens in bakers. Methods: We conducted clinical and immunological evaluations of 81 consecutive bakers reporting occupational symptoms using commercial tests (skin prick test (SPT), specific IgE, ISAC microarray) and six additional dot-blotted wheat allergens (Tri a 39, Tri a Trx, Tri a GST, Tri a 32, Tri a 12, Tri a DH). Results: Wheat SPT resulted positive in 29 bakers and was associated with work-related asthma (p<0.01). Wheat IgE was detected in 51 workers and was associated with work-related asthma (p<0.01) and rhino-conjunctivitis (p<0.05). ISAC Tri a 30 was positive in three workers and was associated with work-related dermatitis (p<0.05). Wheat dot-blotted allergens were positive in 22 bakers. Tri a 32 and Tri a GST were positive in 13 and three bakers, respectively, and both were associated with work-related dermatitis (p<0.05). This association increased (p<0.01) when Tri a 32, Tri a GST and Tri a 30 were analysed together (p<0.01). Wheat IgE levels were associated with work-related dermatitis (p<0.01). Conclusions: Wheat IgE levels and wheat microarrayed allergens may be associated with some occupational allergic phenotypes. The extension of the panel of wheat allergens may be promising for discriminating the clinical manifestations of baker's allergy.